Pengembangan E-Modul Fisika Berbasis Discovery Learning pada Materi Energi Terbarukan untuk Meningkatkan Berpikir Kritis Siswa - Reno Nabila; Endang Lovisia; Sulistiyono Sulistiyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Abstract: This research was carried out with the aim of producing a Physics E-Modul Based on Discovery Learning to improve the critical thinking of class The research carried out is Research and Development (R&D) research using a 4-D approach which includes the definition stage, design stage, development stage and disseminate stage. The subjects of this research are students. class X.5 of SMA Negeri 1 Muara Beliti. Data collection techniques use interviews, observation, questionnaires and test questions. Based on the feasibility test analysis of the E-Module media given by the three experts, namely language, material and media experts, it shows that the physics E-Modul media meets the Very Good criteria, and the critical thinking of class X5 students at SMA N 1 Muara Beliti after using the physics-based E-module Discovery Learning based on the Ngain test is 0.32 in the medium category. Thus, it can be concluded that the Discovery Learning-based physics E-module developed by researchers can improve students' critical thinking in the physics learning process in class. Keywords: E-Modul, Discovery Learning, 4-D, Critical Thinking